2018
DOI: 10.3892/or.2018.6195
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of hnRNP A2/B1 inhibits cell proliferation, invasion and cell cycle triggering apoptosis in cervical cancer via PI3K/AKT signaling pathway

Abstract: Cervical cancer is currently one of the major threats to women's health. The overexpression of heterogeneous nuclear ribonucleoprotein A2/B1 (hnRNP A2/B1) as the biomarker has been investigated in various cancers. In our previous study, we found that lobaplatin induced apoptosis and cell cycle arrest via downregulation of proteins including hnRNP A2/B1 in cervical cancer cells. However, the underlying relationship between hnRNP A2/B1 and cervical cancer remained largely unknown. hnRNP A2/B1 knock-down in HeLa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 40 publications
2
48
1
Order By: Relevance
“…Accumulating evidence has indicated that hnRNPA2/B1 plays a pivotal role in increasing the metastatic propensity of tumor cells [ 10 , 35 ]. Notably, hnRNPA2/B1 has also been reported as an inducer of EMT in liver [ 13 ], pancreatic [ 36 ], and lung cancer cell lines [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has indicated that hnRNPA2/B1 plays a pivotal role in increasing the metastatic propensity of tumor cells [ 10 , 35 ]. Notably, hnRNPA2/B1 has also been reported as an inducer of EMT in liver [ 13 ], pancreatic [ 36 ], and lung cancer cell lines [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, hnRNP A2/B1 has been described in the regulation of alternative splicing of several tumor suppressors and oncogenes, such as Bcl-x [ 13 , 14 , 15 ], which is an anti-apoptotic protein belonging to the well-known Bcl-2 family. Moreover, accumulating evidence also revealed that suppression of hnRNP A2/B1 induced cell cycle arrest at G1 phase in cervical cancer cells [ 16 ], lung cancer cells [ 17 , 18 ], and human embryonic stem cells [ 19 ], which renders it a potential novel target for tumor therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Cervical cancer is one of the most serious malignant tumors, and is associated with high rates of morbidity and mortality, particularly in developing countries, including China. 10 , 11 Worldwide, a large number of new cervical cancer cases are diagnosed every year, and more than half of patients diagnosed died from the cancer. 3 Tumor progression involves tumor cell proliferation and metastasis and novel targeted therapeutic strategies are urgently required for patients with cervical cancer.…”
Section: Discussionmentioning
confidence: 99%